Tetrazine-Induced Bioorthogonal Activation of Vitamin E-Modified siRNA for Gene Silencing - Xueli Zhang; Amu Gubu; Jianfei Xu; Ning Yan; Wenbo Su; Di Feng; Qian Wang; Xinjing Tang (Molecules, 2022)
The temporal activation of siRNA provides a valuable strategy for the regulation of siRNA activity and conditional gene silencing. The bioorthogonal bond-cleavage reaction of benzonorbonadiene and tetrazine is a promising trigger in siRNA temporal activation. Here, we developed a new method for the bio-orthogonal chemical activation of siRNA based on the tetrazine-induced bond-cleavage reaction. Small-molecule activatable caged siRNAs were developed with the 5′-vitamin E-benzonobonadiene-modified antisense strand targeting the green fluorescent protein (GFP) gene and the mitotic kinesin-5 (Eg5) gene. The addition of tetrazine triggered the reaction with benzonobonadiene linker and induced the linker cleavage to release the active siRNA. Additionally, the conditional gene silencing of both exogenous GFP and endogenous Eg5 genes was successfully achieved with 5′-vitamin E-benzonobonadiene-caged siRNAs, which provides a new uncaging strategy with small molecules.